Penalization and multidimensional poverty: improving our understanding of poverty amongst offenders in Ciudad Juarez, Mexico - Chávez Villegas, Cirenia (Crime, law and social change, 2018)
Using a multidimensional approach to poverty measurement, this article aims to contribute to an improved understanding on the main aspects of deprivation experienced by former participants of organized crime in Ciudad Juarez, Mexico, a city that became the epicenter of violence due to the ‘war on drugs’ declared in 2006. A sample of 180 surveys and 20 in-depth interviews were implemented to evaluate multidimensional poverty amongst young men serving a prison sentence for a series of crimes related to organized criminal activity (aged 12 to 29) in Ciudad Juarez, Chihuahua. An equal number of surveys were implemented to a group of non-offenders who had no criminal record and resided in a marginalized area of the same city. The research finds that while offenders fared worse in several non-income dimensions of poverty compared to non-offenders, qualitative evidence revealed that experiences of poverty of offenders were not homogenous, as suggested by existing studies. One of the key findings to emerge from the research is that participation in organized crime decreases income poverty; however, participation did not constitute an effective nor sustained pathway out of poverty nor did it decrease deprivation in other dimensions due to a highly skewed distribution of income in the illegal economy and the use of gains from illegal activity to fuel conspicuous consumption, findings that are similar in the established Western literature on youth gangs.